The complex landscape of human trafficking: a comprehensive exploration with emphasis on legal safeguards for victims in Egyptian and Arab Legislation - El-Kady, Ramy (Modern insights and strategies in victimology, 2024)
Human trafficking victims suffer a direct assault on their fundamental rights, enduring a modern form of slavery and exploitation. Perpetrated by criminal groups, human trafficking exploits victims, especially women and children, in forced labor, prostitution, or organ trafficking, treating them as commodities in a market driven by supply and demand, thereby profiting at the cost of fundamental rights and human dignity. This chapter underscores the critical significance of understanding the multifaceted challenges inherent in combating human trafficking, emphasizing the urgent need for effective measures. By delving into the complexities of the transnational organized structure of this crime, the chapter provides valuable insights into the hurdles faced by law enforcement and investigative agencies. Recognizing the gravity of human trafficking as a direct violation of fundamental rights and human dignity, this chapter aims to contribute to the development of comprehensive strategies and policies to address this pervasive issue.